2016
DOI: 10.1177/1527002514539688
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Winner of Tied National Football League Games

Abstract: We construct a data set of all 429 tied at the half regular season National Football League (NFL) games between 1994 and 2012. We then examine whether or not the path taken to reach the tie (e.g., rushing yards, turnovers, etc.) has any ability to predict the eventual winner. Our main finding is that only the point spread is significantly predictive, although there is weak evidence to suggest that allowing more sacks reduces the chances of winning. Surprisingly, we find that the team receiving the first posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…To address our first set of research questions regarding the accuracy of the spread in predicting the winner of the game we follow Quenzel and Shea (2016) and use a logit model to analyze the accuracy of the spread in predicting the winner of a game. 9 The dependent variable in the logit regressions is an indicator variable taking the value of one if the favored team won and zero otherwise.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address our first set of research questions regarding the accuracy of the spread in predicting the winner of the game we follow Quenzel and Shea (2016) and use a logit model to analyze the accuracy of the spread in predicting the winner of a game. 9 The dependent variable in the logit regressions is an indicator variable taking the value of one if the favored team won and zero otherwise.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In a related paper, Boulier and Stekler (2003) investigate whether the betting market in the NFL can accurately predict which team will win. Similarly, Quenzel and Shea (2016) use the NFL betting market to examine the predictive accuracy of the spread, among other factors, in determining which team will win the game. Thus, we first seek answers to whether the betting line spread accurately predicts the winner of a game, both for regular season and bowl college football games—while conditioning on effects related to conference matchup and momentum.…”
Section: Introductionmentioning
confidence: 99%
“…One study is observed on sport leadership selection [40]. Three papers reflected on match strategy, team selection, match outcome and related areas of strategic relevance in sport [31,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Predictive analytics method is used by seven different studies [7,30,34,35,[38][39][40][41]. Predictive analytics includes different types of econometric and statistical techniques that range from machine learning, classification, multivariate regression and other related techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Робота [42], в свою чергу, присв'ячена дослідженням щодо формування спортивного лідерства. В статтях [43], [44] розглянуто взаємні впливи суміжних стратегічних напрямків застосування аналітичних інструментів, закрема стратегії матчів, вибір команд, результати матчів, тощо. Для вирішення завдань спортивного менеджменту в публікаціях [45], [46], [47] Область застосування [7], [21] Журнал спортивного менеджменту Маркетинг у соціальних мережах [3], [13] Конференція аналітики спортивної аналітики MIT Sloan Аналіз даних у спортивному менеджменті [8] Двадцять друга конференція Америки з питань інформаційних систем, Сан-Дієго Аналіз технологій та даних у спортивному менеджменті [5] Журнал Королівського статистичного товариства Ринок ставок на футбол [38] Журнал спортивного менеджменту Дослідження сприйняття [6] Журнал Королівського статистичного товариства Ринок ставок на футбол [40] Журнал спортивної економіки Виступ команд [43] Журнал спортивної економіки Заробітна плата футболістів [5], [30] Міжнародний журнал спортивного маркетингу та спонсорства Торги на спортивні заходи / турніри [22] Журнал спортивного менеджменту Огляд обсягу [41] Журнал передових досліджень в галузі комп'ютерної та комунікаційної техніки Точність прогнозування [44] Журнал спортивної економіки Функція успіху конкурсу [41] Журнал спортивної економіки Оцінка результативності [35] Малайзійський журнал інформатики Маркетинг та акції [45] Журнал спортивної економіки Конкурентний баланс [46] Журнал спортивної економіки Оцінка ефективності [36] Журнал кількісної аналітики у спорті Аналіз даних для прогнозування результату матчу [39] Журнал спортивної економіки Коефіцієнти ставок [23] Журнал спортивного менеджменту Дослідження обсягу [21] Візуальна інформатика Візуальна аналітика [33] Журнал спортивного менеджменту Споживча інноваційність спортивної команди…”
unclassified